Testing the Weak-Form Market Efficiency in the Indian Stock Market : Evidence from the Bombay Stock Exchange Index (BSE) Sensex - Ryaly, Venkata Rajasekhar; Subba Raju, G. V.; Urlankula, Bhargava (Indian Journal of Finance, 2017)
Performance of the stock markets is considered as a very important tool to measure the performance of the economy. In recent years, the Indian stock market has witnessed a tremendous growth in all the facets of trading , that is, number of companies listed, market capitalization, membership, value of trading ,volume of trading per day, and so forth. The Indian benchmark stock index SENSEX by June 2015 had grown massively to over 27,780.83 from 3,658 in January 1998. This unprecedented growth in the Indian stock market raises the interest over the efficiency of the stock market. The present paper tested the weak-form of market efficiency in the Indian stock market by testing the random walk hypothesis in the return series. According to the random walk hypothesis, the stock movements are random and unpredictable. Weighted index of the Bombay Stock Exchange (SENSEX) was examined for the study from 1998 to July 2015 by using daily data and weekly data. A battery of tests were applied on the data , that is, autocorrelation test, unit root test, and variance ratio test. The empirical evidence found from the autocorrelation test conclusively rejected the serial dependency in the series observed, and hence proclaimed the existence of the random walk hypothesis in the Indian stock market. ADF, DF-GLS, PP, and KPSS tests were performed to find the significance of unit root, and the results from the unit root test were consistent with the autocorrelation test. Similar and very strong evidence was found from the results of the variance ratio test also. Reasonable empirical evidence was found to prove the weak-form of market efficiency in the Indian stock market through this paper.